Practical One-Pot Synthesis of 4,6-Bis(hetero)aryl- and 4-(Hetero) aryl-6-methyl-substituted 1,3,5-Triazin-2-amines - Calheiros, Laís C.; Moura, Sidnei; Back, Davi F.; Paveglio, Guilherme C.; Casagrande, Gleison A.; Pizzuti, Lucas (Synthesis, 2022)
Two series of 4,6-disubstituted 1,3,5-triazin-2-amines were prepared by cesium carbonate-promoted cotrimerization of aromatic nitriles with guanidine and the reaction of (hetero)aryl nitriles with N-acetylguanidine. The first series of 4,6-bis(hetero)aryl-1,3,5-triazin-2-amines was synthesized in yields of 56–85% by adapting a traditional approach that starts from readily available substrates but requires strong and hard-to-handle bases as well as presents serious scope limitations. In this line, the method developed here used a mild base and overcame the scope limitation for p-substituted benzonitrile with electron-releasing group. The second series of 4-(hetero)aryl-6-methyl-1,3,5-triazin-2-amines comprises unsymmetrically substituted symmetrical triazines, which were synthesized in yields of 58–75%. In summary, this work highlighted a synthetic method, which tolerates broad range of substrates, including o- and p-substituted benzonitriles as well as heteroaromatic nitriles.
Keywords: symmetrical triazines; heterocycles; cotrimerization reactions; guanidine; cesium carbonate